Complications and Solutions in Propeller Flap Surgery - Cajozzo, Marta; Jiga, Lucian P.; Jandali, Zaher; Muradov, Mismil; Pignatti, Marco; Cordova, Adriana; D'Arpa, Salvatore (Seminars in Plastic Surgery, 2020)
Propeller perforator flaps (PPFs) have long been proven as valid reconstructive tools for a wide range of soft tissue defects in different body regions. During the last decade, despite their numerous advantages, many authors have thoroughly analyzed outcomes of these flaps, sometimes discouraging their use mainly because of a high failure rate. Accurate patient selection, adequate preoperative planning, and an appropriate dissection technique seem to potentially improve outcomes. Our study provides a review of the relevant literature related to PPF complications and of our experience, describing reasons for failure, measures for preventing them, and approaches for a prompt evaluation and management of complications.
Keywords: propeller flap; perforator flap; reconstructive surgery; risk factors; complications